TiO2 powder photocatalyst from sol-gel route and its immobilisation with cement for photocatalytic phenol removal - Nor Hafizah; Parveen, Jamal; Mohamed Ismail, Abdul Karim, Prof. Dr.; Iis, Sopyan (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/